Kvävemineralisering från stallgödsel beroende på olika grad av inblandning i mark - Jönsson, Erik (2011)
The impact of the distribution in the soil volume of two farm manures on the net mineralization and immobilization processes of nitrogen were studied in an incubation experiment. Cattle slurry and broiler litter were placed in the soil with three procedures for incorporation including placement on top of the soil (TOP), in the middle of the soil (MID) and mixed homogenously with the soil (MIX). During the two weeks of incubation, few significant differences in net mineralization were seen between TOP, MID and MIX. However, there was a tendency that MIX led to a larger net immobilization of N than placement at one point (TOP and MID). This is also the result in the literature. This could be explained by the greater contact between the soil microorganisms and the easily degradable C in the manure when it was mixed with the soil. Hence, my results don’t contradict the literature and point placement of farm manures can improve the utilization of N, although TOP would cause great NH3 losses when applied to field conditions. Therefore, placing the manure at one point a few cm below the surface would result in the best N utilization efficiency.